Léčba zlomenin diafýzy humeru nitrodřeňovou fixací svazkem hřebů dle Hackethala - Obruba, P; Kopp, L; Edelmann, K (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2012)
PURPOSE OF THE STUDY To inform on our experience with the treatment of humeral shaft fractures by intramedullary osteosynthesis using Hackethal's bundle nailing and to evaluate indications for the current use of this technique. MATERIAL AND METHODS From January 2001 to December 2009, a total of 184 patients with humeral shaft fractures were treated surgically and, of these, 147 by Hackethal's nailing. From January 2006 60 patients treated by this technique were prospectively followed up and, of them, 50 were evaluated (83.3%) and included in this study. The average age of the study group was 51.2 years. Fifteen fractures (30%) were in the proximal third, 32 (64%) in the middle third and three (6%) in the distal third of the humeral diaphysis. According to the AO classification, the distal-third diaphyseal fractures were mostly type A2 (26.6%) and type B1 (20.1%) , mid-third fractures were mostly type A3 (31.3%) and distal-third fractures were not evaluated because of their low number. Based on radiographic examination, patients with uncomplicated fractures of the humeral shaft were indicated for surgery. This was performed according to the original Hackethal's procedure with the patient in the prone position using Kirschner wires, 2 mm in diameter, as implants. The patients were followed up at 6 weeks and 3, 6, 9 and 12 months after surgery. On examination, healing of the operative wound, bony union achieved and radiographic findings of the fragment position were evaluated. The range of mo tion at the shoulder and elbow was assessed and subjective patients' feelings were recorded. RESULTS Of the 50 patients evaluated, 45 (90%) healed by first intention, four developed pseudoarthrosis (8%) and one required repeat surgery. No deep wound infection was recorded. Six patients (12%) had humeral angulation up to 10 degrees and one (2%) up to 13 degrees. This angulation was recorded in proximal-third diaphyseal fractures. A deviation in humeral internal rotation was found in two patients (4 %), in one of whom it was 40 degrees. Mild restriction of elbow extension (10 degrees) was found in two patients (4%), five (10%) reported slightly restricted motion of the shoulder and five, chiefly elderly patients with proximal-third diaphyseal fractures, had severe restriction of shoulder motion. Most of the patients (78%) reported full satisfaction, including return to normal daily activities, at 6 months after injury. When the therapy was finished at 12 months after surgery, 44 patients (88%) expressed their full satisfaction. DISCUSSION Our results give support to the previously reported good outcomes of Hackethal's osteosynthesis of the humeral shaft. This method is associated with a minimum of complications if the conditions of correct indication are fulfilled, i.e., uncomplicated fractures of the mid-third humeral diaphysis are considered. Filling the medullary cavity completely with K-wires or nails is an additional condition. Without these being met, good stability of the fracture is not achieved and non-union can develop, as shown by the analysis of cases with non-union in our patient group. CONCLUSIONS Hackethal's technique of osteosynthesis with elastic bundle nailing facilitates safe and easy treatment of uncomplicated diaphyseal fractures of the humerus. Its outcomes are comparable with the other currently used and more expensive methods. It is the method of first choice in the treatment of transverse and short oblique fractures of the mid-third of the humeral shaft. Key words: humeral shaft fractures, bundle nailing, Hackethal's technique.
Keywords: Humans; lidé středního věku; Female; Aged; intramedulární fixace fraktury; dospělí; mladý dospělý; Humeral Fractures; senioři; lidé; fraktury humeru; Bone Nails; Adult; kostní hřeby; ženské pohlaví; Male; Middle Aged; Adolescent; Aged, 80 and over; Young Adult; senioři nad 80 let; mužské pohlaví; Fracture Fixation, Intramedullary; mladiství